Implementation Of A Character Education Program Through 5s Activities (Smile, Greetings, Sapa, Popular, Courteous) At State 100 Primary School Pekanbaru - Yuyun Aulia; Febrina Dafit (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Character education is an attempt to educate students so that they understand, feel and apply good values in their lives. However, in reality there are still some students who do not apply politeness in speaking, the researchers examined further how to implement character education in the 5S program at SDN 100 Pekanbaru. The purpose of this research is to describe the implementation of character education in the 5S program at SDN 100 Pekanbaru. This research method uses descriptive qualitative research methods using interview instruments. From the research results it can be seen that the character values in the 5S program are tolerance, social care and peace-loving values. The 5S program implemented atSDN 100 Pekanbaru makes students behave politely and politely so that students respect each other. Students become helpful, so as to create a comfortable, harmonious and peaceful school environment.